Do Explicit and Implicit Parental Financial Socialization Influence Students’ Financial Literacy? Evidence from India - Subramanian, Rameshkumar; Arjun, T. P. (Indian Journal of Finance, 2024)
Purpose : The present study investigated how explicit and implicit parental financial socialization influenced studentsâ€™ financial literacy (FL). Design/Methodology/Approach : Data were collected from 200 PG students at the Central University of Tamil Nadu, India, using a multiple-stage random sampling technique. Multiple linear regression and an artificial neural network (ANN) analysis were used to identify the most important predictors of FL. Findings : The findings showed that implicit parental financial socialization significantly positively impacted studentsâ€™ FL; whereas, explicit parental financial socialization did not. Additionally, studentsâ€™ FL is not considerably impacted by viewing parents as financial role models. Still, when parents had more income and educational attainment, their children showed a larger degree of FL. Based on the ANN analysis, implicit parental financial socialization was the most significant predictor of studentsâ€™ FL. Practical Implications : The findings emphasized that parents must receive adequate financial education and exhibit responsible financial behavior in order to improve students’ FL and their financial well-being. Originality : The impact of parental financial socialization, both explicit and implicit, on pupilsâ€™ financial literacy in the Indian setting has not, as far as we are aware, been studied in the literature before.